Formation of p-, n-conductivity in semiconductors - Gretchikhin, Leonid I. (Vojnotehnički glasnik / Military Technical Courier, 2017)
The paper considers the energy position of negative ions of impurity atoms in the band gap of a semiconductor. Owing to the Boltzmann law, the energy levels of negative ions in the vicinity of the conduction band supply electrons to the conduction band, while resonance exchange of electrons occurs from the energy levels of negative ions in the vicinity of the allowed terms of the atoms of the main crystal. It is shown how energy band diagrams of n-conductivity and р-conductivity are formed. The applied external electric field acts oppositely on the impurities located in the vicinity of the conduction band and on those located in the vicinity of the allowed energy levels of the atoms of the main crystal. Impurity conductivity is determined by dielectric permittivity formed by the induced electric dipole moments of negative ions.